(untitled) (FULafia Journal of Science and Technology, 2026)
Maize (Zea mays L.) is one of the most significant cereal crops cultivated worldwide and serves as a staple food, animal feed, and industrial raw material. The research was carried out at the Botanical garden of the Federal University of Lafia to evaluate the morph-Nutraceutical compositions of different maize varieties cultivated in Nigeria. The experiment was laid out in a randomly complete block design (RCBD) with replications. Data collected were subjected to analysis of variance (ANOVA) using GenStat software version 18.0. All Morpho-Nutraceutical analysis and procedures were carried out according to AOAC. The result revealed that SAMMAZ 75 had the highest moisture content (9.378 %) while SAMMAZ 51 had the lowest moisture content (6.548 %). The (SAMMAZ 75 had the highest ash content (3.530 %) while SAMMAZ 51 had the least ash content (2.938 %). The % fat content varied significantly, with the highest value of 10.346 % observed in SAMMAZ 75 and the lowest value of 6.475 % in SAMMAZ 51. The percentage crude protein (C.P) ranged from 4.375 % SAMMAZ 52 to 10.937 % (SAMMAZ51). The percentage crude fibre (C.F) ranged from 4.935 % (SAMMAZ 34) to 8.328 % (SAMMAZ 75). The % carbohydrate (CHO) content ranged from 62.168 % SAMMAZ 75 to 70.082 % (SAMMAZ 34). Sammaz 34 sammaz 75 and sammaz 52 are therefore recommended for most of the agronomical, phytochemical and nutritional properties. Keywords: Morpho-nutraceutical, Genetically modify maize, Varieties